Evaluation of internal and external markers for estimating dry matter intake and digestibility in cattle - Velasquez, Alejandro Vargas (2017)
Feed intake assessment is a valuable tool for herd management decisions. The use of markers, either internal or external, is currently the most used technique for estimating feed intake in production animals. Three experiments were conducted with beef and dairy cattle. In dairy cows fed a corn silage based diet with 45% concentrate, the average fecal recovery (FR) of TiO2 was higher than FR of Cr2O3 and both FR were more than unity. The FR was unaffected by the fecal sampling procedure but, estimates for dry-matter digestibility (DMD) and fecal output (FO) were affected. The Cr2O3 + indigestible acid detergent fiber (iADF) marker pair produced accurate dry-matter intake (DMI) estimates. In steers fed diets with different forage sources FR of TiO2 was close to 1 and this marker produced adequate FO estimates. The FR was affected by the forage source that composed the diet and none of the marker pairs produced accurate DMI estimates. In young Nelore bulls fed corn silage or Tifton-85 hay based diets with varying F:C ratios, the average FR of internal markers acetyl bromide lignin (ABL), indigestible neutral detergent fiber (iNDF), iADF and cutin was different from 100%. Markers Cr2O3 and TiO2 had FR lower and higher than 100%, respectively. The combination of internal and external markers to estimate DMI produced satisfactory and accurate results, particularly Cr2O3 based pairs with iNDF and iADF. Internal markers ABL and cutin deserve more attention. The GRAB sampling procedures yielded accurate DMD, FO and DMI estimates, which were as good as or better than BULK sampling procedures. Regardless of the fecal sampling method and the composition of the diet, it is necessary to establish the FR of the markers to be used in each experiment, in order to obtain correct estimates. None of the markers had complete FR consistent throughout the 3 experiments. Cutin and ABL had lower than unity FR on all diets and failed to produce accurate DMD estimates. When either one was paired with Cr2O3 or TiO2, DMI estimates were also not accurate. Of the indigestible fibers, iNDF and iADF, the later was more accurate in estimating DMI when paired with Cr2O3. Consistently throughout the experiments, FR was lower than and higher than unity for internal and external markers, respectively. Corrected FO estimates were accurate for Cr2O3 on various diets under GRAB sampling. The same was not true for TiO2, which even after FR correction was applied failed to produce accurate FO estimates consistently. The method of dosing the external markers is extremely important and greatly affects and determines results. Whichever the method, it must allow the animals to display normal feeding behavior and not affect performance. The GRAB sampling procedures can replace TFC (once FR is established) which may open new possibilities for pasture based or collectively housed animals.